2014
DOI: 10.4161/jkst.28975
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and epithelial–mesenchymal transitions in carcinomas

Abstract: Cellular programs coupled to cycles of epithelial–mesenchymal transitions (EMTs) play critical roles during embryogenesis, as well as during tissue development, remodeling, and repair. Research over the last decade has established the importance of an ever-expanding list of master EMT transcription factors, whose activity is regulated by STAT3 and function to stimulate the rapid transition of cells between epithelial and mesenchymal phenotypes. Importantly, inappropriate reactivation of embryonic EMT programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 97 publications
(176 reference statements)
9
138
0
1
Order By: Relevance
“…Numerous studies have demonstrated constitutive activation of STAT3 in a wide variety of human malignancies, including head and neck, breast, lung, gastric, hepatocellular, colorectal and prostate cancers (27)(28)(29). Aberrantly STAT3 activation contributes to oncogenesis by preventing apoptosis, inducing cell proliferation, angiogenesis, invasion, and metastasis as well as suppressing antitumor immune responses (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated constitutive activation of STAT3 in a wide variety of human malignancies, including head and neck, breast, lung, gastric, hepatocellular, colorectal and prostate cancers (27)(28)(29). Aberrantly STAT3 activation contributes to oncogenesis by preventing apoptosis, inducing cell proliferation, angiogenesis, invasion, and metastasis as well as suppressing antitumor immune responses (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 in metastatic progression is well established and has been associated with myeloid cell recruitment (Chang et al 2013), angiogenesis (Chang et al 2013), epithelial-mesenchymal transition (Wendt et al 2014), and migration (Barbieri et al 2010a). However, its potential role in the maintenance of breast cancer cell homeostasis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, STAT3 mediates its pro-survival functions via Survivin, which not only prevents apoptosis but also promotes the mitogenic activity of cells (73,74). Studies have also shown that STAT3 controls the expression of the master EMT (epithelial-to-mesenchymal) transcriptional regulators, thus, contributing to the process of metastasis in cancers (75). An aberrant expression of STAT3 was also shown to contribute to the tumor progression via facilitating cell motility and invasion (76).…”
Section: Jak/stat Signaling In Gastric Tumorigenesismentioning
confidence: 99%